Prevalence of Panton-Valentine Leukocidin (PVL) and Antimicrobial Resistance in Community-Acquired Clinical Staphylococcus aureus in an Urban Gambian Hospital: A 11-Year Period Retrospective Pilot Study - Darboe, Saffiatou; Dobreniecki, Sarah; Jarju, Sheikh; Jallow, Mamadou; Mohammed, Nuredin Ibrahim; Wathuo, Miriam; Ceesay, Buntung; Tweed, Sam; Basu Roy, Robindra; Okomo, Uduak; Kwambana-Adams, Brenda; Antonio, Martin; et al. (Frontiers in Cellular and Infection Microbiology, 2019)
Background:Staphylococcus aureus is a major human pathogen. Panton-Valentine leukocidin (PVL) is a virulence factor produced by some strains that causes leukocyte lysis and tissue necrosis. PVL-associated S. aureus (PVL-SA) predominantly causes skin and soft-tissue infections (SSTIs) but can also cause invasive infections such as necrotizing pneumonia. It is carried by both community-associated methicillin susceptible S. aureus (CA-MSSA) and methicillin resistant S. aureus (CA-MRSA). This study aims to determine the prevalence of PVL-SA among patients seen at an urban Gambian hospital and associated antibiotic resistance. Methods: Archived clinical S. aureus (70 invasive bacteraemia and 223 non-invasive SSTIs) from 293 patients were retrieved as well as relevant data from clinical records where available. Antibiotic susceptibility was assessed using disc diffusion according to Clinical Laboratory Standards Institute (CLSI) guidelines. Genomic DNA was extracted and the presence of lukF and lukS PVL genes was detected by conventional gel-based PCR. Result: PVL-SA strains accounted for 61.4% (180/293) of S. aureus isolates. PVL prevalence was high in both Gambian bacteraemia and SSTIs S. aureus strains. Antimicrobial resistance was low and included chloramphenicol (4.8%), cefoxitin (2.4%), ciprofloxacin (3.8%), erythromycin (8.9%), gentamicin (5.5%) penicillin (92.5%), tetracycline (41.0%), and sulfamethoxazole-trimethoprim (24.2%). There was no association of PVL with antimicrobial resistance. Conclusion: PVL expression is high among clinical S. aureus strains among Gambian patients. Reporting of PVL-SA clinical infections is necessary to enable the monitoring of the clinical impact of these strains in the population and guide prevention of the spread of virulent PVL-positive CA-MRSA strains. SUMMARY Staphylococcus aureus (S. aureus) is a major human pathogen with several virulence factors. We performed a retrospective analysis to investigate the prevalence of one such virulence factor (PVL) amongst clinical S. aureus samples. We found a high prevalence in our setting but antimicrobial resistance including methicillin resistance was low.